Engaged and critical? The young generation’s political participation in EU countries - Kiisel, Maie; Leppik, Marianne; Seppel Külliki (Studies of Transition States and Societies, 2015)
Within Europe, there is a clear difference in the strength of political activism between old and new member states. Taking Dalton’s differentiation between old and new types of participation, ‘duty’ and ‘engaged’ citizenship, as a point of departure, the article explores the major predictors for the new, network-based and horizontal political practices among young people. The article uses data from the 2006 and 2012 rounds of the European Social Survey to explore country and age group differences within the EU to seek out structural reasons for the trends in duty and engaged citizenship. The results show that duty citizenship is decreasing and engaged citizenship increasing, but the changes are small and not only among youth. Both types of political participation are related to strong evaluations of the performance of democracy. While there are significant differences in value orientations between adult engaged and duty citizens, these differences are less marked in the case of young people.